Bourdieu and Foucault: a conceptual integration toward an empirical sociology of prisons - Schlosser, Jennifer A. (Critical criminology, 2013)
Although the similarities between them are under analyzed, Pierre Bourdieu’s and Michel Foucault’s theories of culture and power are interrelated in some compelling ways. Outline of a Theory of Practice (1977) and Discipline and Punish (1979) are two of the most influential contributions in post-structural and postmodern theory. Yet, far more attention is paid to Foucault’s contributions in criminology than to Bourdieu’s. This essay brings together the work of these influential theorists to argue for a critical examination of the sociology of prisons. Bourdieu’s concepts of: (1) habitus, (2) ethos, (3) doxa, and (4) the theory of practice are related to Foucault’s ideas about (1) discipline, (2) docile bodies, (3) panopticism, and (4) history of the present by comparing specific examples from the original works. Then, the combination of those primary concepts is used to address specific methodological concerns researchers should consider when doing empirical research in prison.